2014
DOI: 10.1016/j.bbabio.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial hyperpolarization during chronic complex I inhibition is sustained by low activity of complex II, III, IV and V

Abstract: The mitochondrial oxidative phosphorylation (OXPHOS) system consists of four electron transport chain (ETC) complexes (CI-CIV) and the FoF1-ATP synthase (CV), which sustain ATP generation via chemiosmotic coupling. The latter requires an inward-directed proton-motive force (PMF) across the mitochondrial inner membrane (MIM) consisting of a proton (ΔpH) and electrical charge (Δψ) gradient. CI actively participates in sustaining these gradients via trans-MIM proton pumping. Enigmatically, at the cellular level g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 43 publications
12
76
0
Order By: Relevance
“…This therefore clearly indicated that DWm was a target of endogenous NO in our cell model. It is worth noting that mitochondrial hyperpolarization has been related to alterations of the oxidative phosphorylation, evidenced by a decrease in cell respiration (Forkink et al, 2014), with concomitant stimulation of glycolysis in order to maintain ATP production (Sánchez-Cenizo et al, 2010). A similar link between reduced mitochondrial activity and shift toward glycolysis due to NO has been previously reported, for example in ovarian cancer cells (Caneba et al, 2014;Chang et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…This therefore clearly indicated that DWm was a target of endogenous NO in our cell model. It is worth noting that mitochondrial hyperpolarization has been related to alterations of the oxidative phosphorylation, evidenced by a decrease in cell respiration (Forkink et al, 2014), with concomitant stimulation of glycolysis in order to maintain ATP production (Sánchez-Cenizo et al, 2010). A similar link between reduced mitochondrial activity and shift toward glycolysis due to NO has been previously reported, for example in ovarian cancer cells (Caneba et al, 2014;Chang et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, this coincidence could be due to respiratory control, which intrinsically reduces respiration during mitochondrial hyperpolarization to prevent excessive ROS production [4042]. Alternatively, it was shown that CI inhibition in HEK293 cells results in a hyperpolarization of mitochondrial membrane potential [43]. Thus, it might be cell-specific characteristics, indicating a defect in complex I respiration in APP-overexpressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of increased CCO activity (to sustain adequate rates of Cyt c oxidation in a less oxidative environment), higher NQO activity could result in the progressive over-reduction of the CoQ pool as well as an altered IMM polarisation state (Abele et al, 2007). These phenomena are common features of heat-or hypoxia-induced stress and, in addition to inhibiting ATP synthesis (Bagkos et al, 2014;Forkink et al, 2014), they promote superoxide generation through mETC III activity, ubiquinol autoxidation and/or NQO dysfunction (Boveris and Chance, 1973;Turrens and Boveris, 1980;Miwa and Brand, 2003;Yin et al, 2010). However, we observed no corresponding increases in host SOD activity, suggesting that (a) no O 2 − -driven oxidative challenge arose, and/or (b) constitutive SOD abundance was sufficiently protective.…”
Section: Discussionmentioning
confidence: 99%